(untitled) (Fractal: Journal of Psychology, 2009)
This text relates to communication and ways of communicability involved in the NTCIs world. It tries to surpass the effects of an alreday installed discursivity which states that in this environment life and creation nurture one another. We discuss the concept of micro politics in a technological net which can be done through expressive hetorogenicity, all this text uses a reference of Gilles Deleuze and Félix Guattari . It relates to a politics operated between warriors and high-tech soldiers who are able to introduce a type of (in) discipline in the discursive chains established in computer based environments, in an attempt to effectively turn them into a locus of production of difference.